Intellectual Traditions, Islamic Reform and Nationalism in the Mzab - Ghazal, Amal N. (2013)
This paper discusses the role of North African Ibadis, Mzabis in particular, in movements of religious reform and nationalism in the nineteenth and twentieth centuries. It unravels the intellectual networks in which Mzabis had been integrated since the late nineteenth century and that spanned from North Africa to East Africa and Oman. Mzabis’ membership in such networks highlighted the reformist trends within Ibadism that led to a rapprochement with the other sects of Islam. This also consequently facilitated the assimilation of Mzab and of Mzabis into the nationalist movements of Algeria in which Mzabis played a leading and formative role. Sources include manuscripts from the Mzab valley, Mzabi newspapers and French archival material.
Keywords: Réformisme – Mzab

Tensions of nationalism: The Mzabi student missions in Tunis and the politics of anticolonialism - Ghazal, Amal N. (International Journal of Middle East Studies, 2015)
Abstract This article examines the significant yet largely overlooked role of the Mzabis, a community from the northern edges of the Algerian desert, in Algerian and Tunisian anticolonialism and nationalism. In so doing, it pursues two aims: first, to shed light on the importance of Tunis to the politicization of the Mzabis in the 1920s and to their induction into local and regional anticolonial and national movements; and second, to highlight the tensions of subsuming regional identities into overarching national identities by focusing on Mzabi political activists’ negotiation of the relationship between the Mzab and Algeria as a national project. The article also explores the spectrum of political possibilities and alternatives envisioned by Mzabis as they participated in religious reform, anticolonial, and nationalist movements. This spectrum, I argue, conveys the fluid relationship between local, national, and regional identities, thus undermining teleological readings of national identity formation.
Keywords: Réformisme – Mzab